Youth participation in disaster risk reduction through science clubs in the Philippines. Issue 2 (28th November 2014) - Fernandez, Glenn; Shaw, Rajib
<x xml:space="preserve">Abstract</x> With the UN‐led celebration of the International Year of Youth from August 2010 to August 2011 there has been a renewed interest in young people and the vital role they can play in important issues, such as disaster risk reduction (DRR). This study aims to examine the potential of science clubs as a vehicle for youth participation in DRR in the Philippines. A questionnaire survey was conducted to obtain quantitative and qualitative data. A total of 658 science club members from different provinces of the Philippines participated in the survey. The result of the survey is used to explain how the major barriers to youth participation in DRR can be overcome. Through science clubs, the youth can become a link between their school, home and community and can contribute to spreading knowledge about disaster prevention, preparedness and response learned inside and outside the classroom.